Tumor microenvironment-responsive nanoplatforms for enhanced cancer immunotherapy: Advances and synergistic strategies - Jie Wu; Xiangdong Xue; Haijing Qu (Nano TransMed)
Despite remarkable advancements in cancer immunotherapy, its clinical efficacy remains constrained by challenges including insufficient tumor accumulation of immunotherapeutics, limited patient response rates, and immune-related adverse events. Tumor microenvironment (TME)-responsive nanoplatforms have emerged as a promising strategy to address these limitations, which could respond to endogenous signals in tumor cells to achieve precise targeting, controlled drug release, and reversal of tumor immunosuppressive microenvironments. Herein, this article systematically reviews TME-responsive design strategies based on intrinsic tumor-specific features, including acidic pH, elevated reactive oxygen species (ROS) levels, reductive conditions, hypoxia, and overexpressed enzymes. Furthermore, we elucidate synergistic mechanisms of TME-responsive nanosystems empowering immunotherapy: i) subcellular organelle-specific delivery, ii) TME remodeling, iii) immunometabolic reprogramming and iv) lymph node drainage regulation. Finally, the current challenges and future directions for clinical translation of these advanced nanomedicine-based immunotherapeutic strategies are discussed, providing insights for the development of next-generation cancer immunotherapies.